Associated factors with taking mammography in peruvian women: a secondary analysis from Familiar Health Demographic Survey, 2015 - Alegría-Delgado, Diana (2019)
Introduction: Breast cancer is the most common type of cancer in women. In Peru, it is the second leading cause of death by cancer. Objective: To determine the sociodemographic factors associated with taking mammography in Peruvian women. Methods: A cross-sectional study. Data of women (40-49 years-old) were selected from Demographic and Family Health Survey databases in 2015. Studied factors included educational level, civil status, educational level and age from partners, marriage age, wealth index, place of residence, and natural region. Results: 2183 women were included, 57,6% reported having full secondary school, 64% had a partner, 24,8% were very poor, and 72,1% lived in rural areas. The factors associated with taking a mammogram were having a partner with higher education, marriage age of 25 years and older, and urban residence (coast and Metropolitan Lima). Conclusions: According ENDES 2015, only 16.9% of Peruvian women between the ages of 40 and 49 have had a mammography, with associated sociodemographic factors.